ASSESSMENT OF ANTHROPOGENIC IMPACTS ON AQUATIC ECOSYSTEMS OF THE SOUTHERN ARAL SEA REGION BASED ON ENVIRONMENTAL RISKS - Raikhan Yusupovna Kalimbetova (European Science Publishing, 2024)
The article is devoted to the assessment of anthropogenic impacts on the ecosystems of the Southern Aral Sea region. The issues of environmental regulation of the so-called permissible load on the Aral Sea ecosystems are considered.
Keywords: Ecosystems, South Aral Sea region, rationing, biodiversity, anthropogenic factor, sustainability.